An ultra hydrophilic dendrimer-modified magnetic graphene with a polydopamine coating for the selective enrichment of glycopeptides. Issue 44 (9th October 2015) - Wang, Yanan; Wang, Jiaxi; Gao, Mingxia; Zhang, Xiangmin
Abstract : A novel ultra hydrophilic dendrimer-modified magnetic graphene@polydopamine@poly(amidoamine) (magG@PDA@PAMAM) was synthesized for the efficient and selective enrichment of N-linked glycopeptides. Abstract : In recent MS-based glycoproteomics, the selective enrichment of glycopeptides from complex biological samples is essential. In this work, for the first time, a novel ultra hydrophilic dendrimer-modified magnetic graphene@polydopamine@poly(amidoamine) (magG@PDA@PAMAM) was synthesized via three simple and rapid steps. The magnetic composites combined large surface of graphene, strong magnetic responsiveness of Fe3 O4 with double hydrophilic abilities of PDA and PAMAM. Especially PAMAM had long dendritic chains and abundant amino groups. When it was grafted onto magG@PDA, it strongly enhanced the hydrophilic properties of the magnetic composites. The PAMAM-functionalized magnetic composites were employed in the enrichment of glycopeptides, 15 glycopeptides from horseradish peroxidase (HRP) digestion were identified and the limit of detection was as low as 1 fmol μL −1 . Also, it showed a good selectivity when the background nonglycopeptides had a concentration 100 fold higher than the target glycopeptides. All the results proved that magG@PDA@PAMAM has great potential in the glycoproteome analysis of complex biological samples.